Holocene Eolian Activity in South-central Saskatchewan and the Southern Canadian Prairies - Wolfe, Stephen; Ollerhead, Jeff; Lian, Olav (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThe chronology and stratigraphy of eolian deposits at two sites in south-central Saskatchewan were studied in order to extend the spatial and temporal record of dune activity on the Canadian prairies. Optical ages document the timing of valley-infilling by sand dunes in the Qu’Appelle River area, and of cliff-top eolian deposition along the South Saskatchewan River. These ages, along with published radiocarbon and optical ages, are used to develop a chronology of eolian activity for south-central Saskatchewan. Optical ages of eolian sands ranging from 5.7 to 0.14 ka (before AD 2000), with intervening paleosols, indicate alternating periods of eolian activity and dune stability during the late Holocene, supported by published radiocarbon ages. Other published radiocarbon ages ranging from 11.3 to 8.4 cal ka BP indicate early Holocene eolian activity. Mid-Holocene ages are predominantly absent from the chronology and this is interpreted as being due to extensive eolian reworking during at least the latter part of the mid-Holocene. The chronology in south-central Saskatchewan is similar to other parts of the southern Canadian prairies. It is likely that preserved mid-Holocene eolian deposits occur within depositional basins in the southern Canadian prairies, and at sites near the southern boreal forest boundary with the prairie ecozone.